Prevalence of Helminthiasis in the Gastrointestinal Tract in Beef Cattle in Bandar Lampung Smallholder Farm - Pertiwi, Vindo Rossy; Putri, Dwi Desmiyeni; Noviadi, Riko; Candra, Agung Adi; Saputra, Ahmad Kurnia; Sofiana, Anjar (Jurnal Sain Peternakan Indonesia, 2026)
Beef cattle are one of the livestock species that contribute significantly to the animal protein supply. Helminthiasis is a parasitic disease that infects cattle worldwide. Although it rarely causes severe clinical illness, it may result in substantial economic losses for farmers. These losses are primarily associated with increased morbidity and, in severe cases, mortality, thereby reducing productivity and growth performance. This study aimed to determine the prevalence of helminthiasis in beef cattle raised in smallholder farms in Bandar Lampung City. A proportionate stratified random sampling method was applied, with a sample size of 10% of the total livestock-owning population across 17 sub-districts. A total of 110 faecal samples were collected from 89 farms. Samples were examined using sedimentation and McMaster techniques. The results showed that 61 (55.5%) cattle were positive for gastrointestinal helminths. Identified parasites included Nematoda (Haemonchus sp., Oesophagustomum sp., Strongyloides sp., Bunostomum sp., Trichuris sp., Mecistocirrus sp., Trichostrongylus sp., Ascaris sp.), Trematoda (Fasciola sp., Paramphistomum sp.), and Cestoda (Moniezia sp.).